Integration of Visual Arts, Music, and Performing Arts through Folk Costume Design Based on the Thinking School Approach: A Case Study of Huai Yang Long Drum Culture for Grade 6 Students - Pansanga, Pranitan; Bhiasiri, Siribhong (An Online Journal of Education, 2026)
This research aimed to: 1) investigate the students' practical skills in visual arts, music, and performing arts following the implementation of integrated learning management based on the Thinking School approach; 2) compare their post-learning academic achievement against the 70% criterion; and 3) evaluate student satisfaction with the learning management. The sample, selected via purposive sampling, consisted of 13 grade-6 students at a school in Khon Kaen province. They were purposefully chosen due to their situated presence within the local cultural context and their readiness to participate in practical activities. The research instruments included 1) four integrated learning plans totaling 8 hours, 2) a practical skill assessment form, 3) an academic achievement test, and 4) a satisfaction evaluation form. Data were analyzed using percentage, mean (M), and standard deviation (SD). The findings revealed that: 1) the students' overall integrated practical skills were at the highest level (M = 3.82, SD = 0.30) 2) the average academic achievement score was 15.62 out of 20, accounting for 78.10%, which exceeded the established 70% criterion; and 3) the students' overall satisfaction with the learning activities was at the highest level (M = 4.79, SD = 0.45). A pivotal discovery of this study is the “Functional aesthetic integration model.” By linking the three artistic disciplines through costume design—balancing aesthetic appeal, musical functionality, and the principles of performing arts movement—this model facilitates meaningful learning and instills a sustainable awareness of local identity among the learners.